Systematic Literature Review : Penerapan Model Game Based Learning (GBL) Pada Mata Pelajaran Matematika - Ade Dwi Oktaviani Oktaviani; Meiliasari; Wardani Rahayu (Gammath : Jurnal Ilmiah Program Studi Pendidikan Matematika, 2026)
This study aims to systematically examine the implementation of Game-Based Learning (GBL) in mathematics education through a Systematic Literature Review (SLR) of empirical studies published between 2020 and 2025. The review process was conducted in accordance with the PRISMA method, which include the stages of identification, screening, eligibility, and inclusion. A total of 10 articles were selected from reputable databases based on predefined inclusion and exclusion criteria. The analysis focused on publication trends, educational levels, and the learning competencies addressed in GBL research.  The findings indicate an increasing trend in GBL-related publications, with predominant implementation at the primary and lower secondary education levels. Most studies suggest that GBL is positively associated with improvements in students’ learning motivation, academic achievement, and critical thinking skills. In addition, GBL has the potential to support the development of students’ social, emotional, and cognitive skills through interactive and engaging learning environments. Therefore, GBL can be considered a promising alternative instructional strategy to address students’ disengagement in mathematics learning and to support the achievement of 21st-century learning goals, particularly in fostering creativity, collaboration, and problem-solving skills.